Qualidade de silagem de BRS Capiaçu (Cenchrus purpureus (Schum.) Morrone), com adição de resíduo de panificação - Guimarães, Weslen Vitor Gomes (Brasil, 2024)
Agriculture is an important activity for Brazil's economy based on imports and exports. Livestock farming in Amazonas shows increasing development in production, where it has around 1,558,283 heads of cattle and 113,557 heads of buffaloes. The seasonality of forage is a challenge linked to animal production, however, to minimize the effects harmed by the quantitative and qualitative depreciation of forage, excess forage production in floods is capable of being used in drought with the introduction of alternatives for forage conservation. such as the ensiling process. The Amazon is characterized by two distinct ecosystems, where it has a dry period and a flood period, and seasonality is one of the challenges Ensiling surplus forage production during the rainy season of the year is an important viable alternative to be supplied for feeding ruminants in the dry period. In this context, considering the rapid expansion of BRS Capiaçu (C. purpureus (Schum.) Morrone) cultivation in Brazil linked to the growing interest in the possibilities and viability of using BRS Capiaçu (C. purpureus (Schum.) Morrone) silage , with different levels of Bakery Waste. The 4 treatments were evaluated with 5 repetitions of 0%, 10%, 20% and 30% of Bakery Residue levels. The aerobic stability of the silage was not influenced during the 72 hours in contact with air, that is, it remained stable without exceeding an elevation greater than 2ºC above the ambient temperature, which was 23.4ºC to 23.9ºC. to this result due to its good state of conservation. It is concluded that the inclusion levels of Bakery Waste at the time of ensiling BRS Capiaçu, improves the chemical composition of the silage in relation to the increase in dry matter, crude protein as well as the pH¹ which remained ideal, as well as an increase in beneficial bacteria. for the fermentation process, which in fact increased the aerobic stability time after opening the silos.